2013
DOI: 10.1055/s-0033-1337905
|View full text |Cite
|
Sign up to set email alerts
|

Energy Expenditure in Rock/Pop Drumming

Abstract: Despite the vigorous nature of rock/pop drumming, there are no precise data on the energy expenditure of this activity. The aim of this study was to quantify the energy cost of rock/pop drumming. Fourteen male drummers (mean?SD; age 27?8 yrs.) completed an incremental drumming test to establish the relationship between energy expenditure and heart rate for this activity and a ramped cycle ergometer test to exhaustion as a criterion measure for peak values (oxygen uptake and heart rate). During live concert per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Calories expended were shown to have a mean of 518 kcal·hr -1 . This was lower compared to the rock/pop drum study, which reported an estimated 600 kcal·hr -1 (De La Rue et al, 2013). By comparison, a study which investigated the performance on of various styles of piano playing, found a mean VO2 of 8.65 ± 2.55 ml·kg·min -1 and 55% of the heart rate age predicted max reached.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Calories expended were shown to have a mean of 518 kcal·hr -1 . This was lower compared to the rock/pop drum study, which reported an estimated 600 kcal·hr -1 (De La Rue et al, 2013). By comparison, a study which investigated the performance on of various styles of piano playing, found a mean VO2 of 8.65 ± 2.55 ml·kg·min -1 and 55% of the heart rate age predicted max reached.…”
Section: Discussionmentioning
confidence: 63%
“…Musicians generally possess athletic similarities, with repetitive movements and high oxygen consumption (VO2) demands. Oftentimes they require a high metabolic demand in order to perform their specific instruments in a fast-paced, long duration, and intermittent environment (De La Rue, Draper, Potter, & Smith, 2013;Holmes & Redding, 2001;Iñesta, Terrados, Garia, & Perez, 2008;Mulcahy et al, 1990;Nietzsche, Stutzig, Walther, & Siebert, 2015;Robertson, Federoff, & Eisensmith, 2010;Salvalaio, Silva, Pinho, & Pohlmann, 2011;Smith, Burke, Draper, & Potter, 2008). Due to the increased beats·min -1 of their genre's songs, a heavy metal musician must presumably sustain a particularly high metabolic rate when playing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study (Amad et al, ) found significant functional connectivity changes following 24 sessions of drum training (three sessions per week for 8 weeks) with an n of 31 ( n = 15 training, n = 16 controls). As drumming is a cardiovascular‐demanding bilateral coordinative exercise (De La Rue, Draper, Potter, & Smith, ) (comparable to NMT more generally) and the study by Demirakca et al () was multimodal (i.e., cognitive, visual, and coordinative demands akin to aNMT), we aimed to enroll a similar number of participants in this preliminary investigation ( n ~ 30).…”
Section: Methodsmentioning
confidence: 99%